Value Relevance and Components of Deferred Tax Assets and Liabilities: Evidence from the Listed Companies on SET 100 in Thailand - Acaranupong, Kittima (Asian Journal of Business and Accounting, 2010)
This paper examines the components of deferred tax assets and liabilities for early adopters of the proposed Thai Accounting Standard (TAS) No. 12 Income Taxes which is expected to be adopted in 2013. It also investigates the value relevance of deferred tax assets and liabilities information for early adopters and non-early adopters of the proposed standard. The result indicates that the main components of deferred tax assets are taxable loss carryforward while those of deferred tax liabilities are deprecation. Using the Feltham- Ohlson (1995) Model for the period from 2004 to 2008, this research reveals that deferred tax assets and deferred tax liabilities are value relevant information for early adopters whilst only deferred tax assets are value relevant information for non-early adopters. The results from this study also support the notion that the adoption of International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) in Thailand will improve the relevance of financial statements. Furthermore, it will enhance the comparability of the financial statements of the Thai listed companies with that of listed companies in foreign countries.